ナンキョク ニオケル ジンコウ ジシン カンソク ノガイヨウ - 伊神, 煇; イカミ, アキラ; 一ノ瀬, 洋一郎; イチノセ, ヨウイチロウ; 原田, 道昭; ハラダ, ミチアキ; 神沼, 克伊; カミヌマ, カツタダ; Ikami, Akira; Ichinose, Yoichiro; Harada, Michiaki; Kaminuma, Katutada (1980)
P(論文) 日本の南極観測は,第20次隊から3年間地学部門の観測に重点がおかれ,人工地震観測も実施されることになった.これは,南極大陸の地下構造の解明と南極における資源探査の基礎技術開発を目的とした日本隊では初めての試みである.第20次隊では南極という特殊条件の下での爆破方法,観測方法,ボーリング方法の検討などを兼ねた予備観測が実施された.第21次隊で本観測が実施される.本報告は,第20次夏隊によって行われた人工地震観測の準備から実施までの報告である.測線は昭和基地付近のオングル海峡から東へ約70kmで,観測点は大陸内に約5km間隔で10点設けた.爆破はオングル海峡と側線東端の内陸の2点で行い,オングル海峡では110m下の海中で火薬1ton,内陸では氷雪ボーリングによる内径14cm,深さ62.8mの孔中に装てんされた火薬560kgの爆破が実施された.爆破および観測は成功し,所期の目的は達成された. The summer-field party of the 20th Japanese Antarctic Research Expedition (JARE-20) carried out the experiments with the explosion seismic method at the Soya Coast in Antarctica. The purpose of the present experiment in Antarctica is to investigate the crustal structure and to establish the technique of the seismic prospecting in Antarctica, such as the laying of profiles and instrumentation, development of ice drills, dynamite for the use at low temperatures, etc. The observation was conducted by 8 persons for a period of 19 days. The profile is about 70 km in length eastward from the Ongul Strait near Syowa Station. Ten observation points were set up every five kilometers along the profile in the Soya Coast. Shot points are located at both ends of the profile. Dynamite of 1000 kg in weight was blasted at the depth of 110 m in the Ongul Strait. On the other side of the profile, a total of 560 kg dynamite was installed from the depth of 17 m to the bottom (62.8 m). The experiment was successful. departmental bulletin paper